(untitled) (International Journal of Engineering and Computer Science, 2014)
The electric drive systems used In Industrial applications are increasingly required to meet higher performance and reliability requirements. The DC Motor is an attractive piece of equipment in many Industrial applications requiring variable speed and load characteristics due to its ease of controllability. Microcontrollers provide a suitable means of meeting these needs. In this paper, Implementation of the AT89C51 Microcontrollers for speed control of DC motor fed by a DC chopper has been investigated. The chopper is driven by a high frequency PWM signal. Controlling the PWM duty cycle is equivalent to controlling the motor terminal voltage, which In turn adjust directly the motor speed. The paper is designed to develop a speed control system for a DC motor using microcontroller PIC AT89C51. The motor is operated in four quadrants i.e. clockwise; counter clock-wise, forward brake and reverse brake. It also has a feature of speed control.